Sonography of Cerebral Infarction in Infancy - Hernanz-Schulman, Marta; Cohen, Wendy; Genieser, Nancy B. (American Journal of Neuroradiology, 1988)
Six infants with cerebral infarcts were examined prospectively with real-time sonography to determine the sonographic characteristics of infarcts and their evolution. Patients' ages ranged from 1 day to 7 months, and serial sonographic and/or CT scans were obtained over a period of 2 weeks to 14 months in the survivors. Among our patients the most characteristic sonographic findings of infarction were absence of gyral definition, absence of vascular pulsations, altered parenchymal echogenicity, and territorial distribution. Mass effect, reflected in ventricular size and shift of midline structures, may also be seen and largely parallels the extent of the infarction. Evolution of infarcts was seen sonographically as gradual return of arterial pulsations and concurrent development of cystic spaces. Sonography was found to be a valuable tool in the diagnosis of infarction in infancy and in monitoring its evolution, although CT was necessary for adequate initial evaluation in older infants.